Mitochondrial BKCa Mediates the Protective Effect of Low-Dose Ethanol Preconditioning on Oxygen-Glucose Deprivation and Reperfusion-Induced Neuronal Apoptosis - Su, Fang; Yang, Huajun; Guo, Anchen; Qu, Zhengyi; Wu, Jianping; Wang, Qun (Frontiers in Physiology, 2021)
Ischemia-Reperfusion (I/R) injury contributes to the morbidity and mortality of ischemic strokes. As an in-vitro model, oxygen-glucose deprivation and reperfusion (OGD/R) exposure induces the neuronal injury. Low-dose ethanol preconditioning (EtOH-PC) was reported to alleviate the neuronal apoptosis during OGD/R. However, whether mitoBKCa channel is involved in the neuroprotective effect of EtOH-PC during OGD/R is not clearly defined. Our present study attempts to explore the mediation of mitoBKCa channel in neuroprotective effect of EtOH-PC on OGD/R induced neuronal apoptosis and the underlying mechanisms. OGD/R model was established using primary cortical neurons which were preincubated with ethanol. Subsequently, the cell viability was measured by CCK-8 assay and the apoptotic cells were determined by TUNEL assay. Annexin V/7-AAD staining and mitochondrial membrane potential using JC-10 were detected by flow cytometry. Western blot was performed to check the apoptosis related proteins. In the mixed primary culture, 95% Neurofilament-positive cells were cortical neurons. Low-dose ethanol preconditioning (10 mmol/L) for 24 h significantly attenuated the OGD2h/R 24h-induced neuronal apoptosis through activating BKCa channel. Further investigations suggested that ethanol pretreatment increased the mitochondrial membrane potential (MMP) and downregulated the production of cleaved caspase 3 in OGD/R-injured neurons by activating mitoBKCa channel. Low-dose ethanol pretreatment significantly attenuated the OGD/R-induced neuronal apoptosis mediated by mitoBKCa channel which modulated the mitochondrial function by impeding the uncontrolled opening of mitochondrial permeability transition pore (MPTP).